Komiks [videorecording] - Hermano, Teresita Z.; del Mundo,Clodualdo ([Manila] Communication Foundation for Asia)
A documentary on the colorful comics industry. It shows the process of producing comics, with interviews of popular writers, illustrators, publishers, editors, distributors and readers.
Narrator, Bibeth Orteza
Keywords: Comic books, strips, etc. -- Philippines; Journalism; Mass communication